PERAN MAHMUD GHAZNI TERHADAP PERKEMBANGAN PERADABAN ISLAM, 388-421 H/ 998-1030 M - Rahmawati Rahmawati; Nor Huda; Otoman Otoman (Tanjak: Sejarah dan Peradaban Islam, 2021)
The topic of this research needs to be investigated because at that time there were many events related to the description of the struggle of many Islamic figures in advancing Islam, especially Mahmud Ghazni. During the reign of Mahmud Ghazni Islamic civilization experienced rapid progress and during the reign of Mahmud Ghazni much progress in the fields of education and the economy. Mahmud Ghazni was a man who controlled Islam and had a lot of influence and power during wars and often won over his enemies until the caliph Al-Qadir Billah gave him the title Yamin addaulah which means people who are trusted by the government and Amin Addaulah which means trusted by the government. Mahmud Ghazni is known as a pious person and has a strong promise in the field of science and development. The problems discussed in this study are as follows. First, what is the general picture of the Ghaznavid dynasty in Islamic history? Second, how was the development of the Ghaznawiyah dynasty during the reign of Mahmud Ghazni? Third, what is the strategy used by Mahmud Ghazni in advancing Islamic civilization? In this study, the type of research used is qualitative research that relies on library materials that are relevant to the research theme, while the method used is historical research, which seeks to find out and make a systematic and objective reconstruction of past history related to the role of Mahmud Ghazni on the development of Islamic civilization (388-421 H / 998-1030 AD), by collecting, evaluating strong evidence to establish facts and get strong conclusions. The results of the research in this study are first, Alpataqin was the pioneer of the founding of the Ghaznawiyah Dynasty, while Sabuktaqin was able to form an established dynasty power and a wide area so that it was later recognized by Baghdad. Second, the government of the Ghaznawiyah dynasty experienced glory during the reign of Mahmud Ghazni who ruled for approximately 34 years. Its power can be used to expand its territory to reach the territory of India, to successfully conquer Peshawar, Kashmir, and Bathinda in 391-394 H/1001-1004 AD. Punjab was controlled in 1006 AD, Kangra in 1009, Baluchistan in 402-403 H. /1011-1012 AD, then Delhi in 405-406 H/1014-1015 AD. The vast territory and abundant sources of wealth make this country's economy very strong, so that it can be used for the prosperity of the country. First, Alpataqin was the pioneer of the founding of the Ghaznawiyah dynasty, while Sabuktaqin was able to form an established dynasty and a large area that was later recognized by Baghdad. Third, Mahmud Ghazni in advancing Islamic civilization in India, carried out several strategies to be able to achieve the heyday and progress of Islam. Mahmud Ghazni's strategy is to advance Islamic civilization in India by carrying out policies in the fields of politics and government, in the military field, carrying out several policies in the economic field as well as policies in the socio-cultural and religious fields.